2019
DOI: 10.1108/aaaj-10-2015-2266
|View full text |Cite
|
Sign up to set email alerts
|

Diverse accounting standards on disclosures of Islamic financial transactions

Abstract: Purpose Since International Financial Reporting Standards (IFRS) are not primarily meant for the accounting needs of Islamic banks, the Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) was established to develop specific accounting standards for Shari’ah compliance. The purpose of this paper is to assess the de jure harmonisation between the disclosure requirements of the IFRS-based Malaysian Accounting Standards (MAS) and those of the AAOIFI. Design/methodology/approach Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The research methods adopted by the 46 papers can be divided into four attributes. The first three are empirical in nature as follows: based on secondary data (Elgattani and Hussainey, 2020; Harun et al , 2020); based on primary data (Nor Farizal et al , 2019); empirical studies that used surveys/questionnaire (Ahmad and Daw, 2015; Ben Abd El Afou, 2017); and theoretical studies that used descriptive analysis for standards and showed the variances by comparing with other standards (Umar and Kurawa, 2019; Ahmed et al , 2019). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The research methods adopted by the 46 papers can be divided into four attributes. The first three are empirical in nature as follows: based on secondary data (Elgattani and Hussainey, 2020; Harun et al , 2020); based on primary data (Nor Farizal et al , 2019); empirical studies that used surveys/questionnaire (Ahmad and Daw, 2015; Ben Abd El Afou, 2017); and theoretical studies that used descriptive analysis for standards and showed the variances by comparing with other standards (Umar and Kurawa, 2019; Ahmed et al , 2019). …”
Section: Resultsmentioning
confidence: 99%
“…theoretical studies that used descriptive analysis for standards and showed the variances by comparing with other standards (Umar and Kurawa, 2019; Ahmed et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…or(3) commits an offence and shall, on conviction, be liable to imprisonment for a term not exceeding eight years or to a fine not exceeding twenty-five million ringgit or to both". Subsection 1 revolves around the significance of Shariah compliance while subsection 3 suggests remedial measures to manage Shariah-non compliance risk.…”
mentioning
confidence: 99%